Should micturating cystourethrogram be routinely performed for paediatric pyeloplasty patients?. (March 2019) - Sim, Siam Wee; Li, Fay Xiangzhen; Oo, Mon Mon; Narasimhan, Kannan Laksmi; Jacobsen, Anette Sundfor; Yap, Te-Lu
Objective: Micturating cystourethrogram (MCUG) has traditionally been recommended as part of the preoperative evaluation of all cases of hydronephrosis. Several studies have shown that the majority of cases with pelviureteric junction obstruction (PUJO) and concomitant vesicoureteral reflux (VUR) were of low-grade and generally resolved spontaneously. We therefore retrospectively evaluated the need for routine MCUG in all cases of PUJO. Methods: We conducted a retrospective review of clinical records of all patients who underwent pyeloplasty in our institution between 2003 and 2015. Data collected included patient demographics, clinical presentation, radiological procedures performed, operative details as well as postoperative outcomes. Results: A total of 119 patients underwent pyeloplasty for PUJO during this study period. MCUG was performed in 88 patients (74%), of whom eight patients had VUR. All eight patients had unilateral PUJO and two patients had bilateral VUR. Only two patients had high-grade VUR (grade 4). These two patients also had hydroureter detected on ultrasound scan (US). All patients with VUR had spontaneous resolution of reflux. While comparing outcomes for patients with and without VUR, there was no statistically significant difference in terms of the need for redo surgery and improvement in differential renal function post-pyeloplasty. Conclusion: The outcome of pyeloplasty appears to be independent of the presence of concomitant VUR. Therefore, we conclude that MCUG does not need to be performed routinely for all PUJO patients. However, patients with history of recurrent urinary tract infection or findings of hydroureter on US should still be investigated with MCUG.